THE MAIN FACTORS OF THE FORMATION AND DEVELOPMENT OF FURNITURE DESIGN - Стрілець, В. Ф. (Art and Design, 2019)
The purpose of this article is the definition of factors that influence the development of modern furniture design and trends in its development in the context of the formation of the subject-spatial environment. The methodology of this study is to apply general scientific methods of analysis, synthesis, comparative analysis, field surveys, experimental design, as well as study of cultural heritage for this research problem. The main groups of factors influencing the formation and development of modern furniture design, which are: socio-economic, ecological, ergonomic, functional-typological, technical, historical-cultural, aesthetic, are revealed and analyzed. These factors and the conditions for their change are distinguished by the various dynamics of development over time, as well as by the different nature of the influence on the formation of furniture design. Given the dynamics and prospects of the changes, the peculiarities of factors influence on the development of furniture design in the subject-spatial environment are highlighted. This approach has allowed to determine the modern trends in the development of furniture design. The scientific novelty of the work consists in identifying and highlighting the main factors shaping and developing the design of modern furniture and the characteristics of their influence on the shaping of furniture, installing on the basis of this basic trends in the development of furniture design in the late 20th and early 21st centuries. The practical significance. Identified and summarized the main factors in the formation of furniture and the identified trends in the development of their design will be useful for modern practice of designing and producing furniture and will open up opportunities for further in-dept scientific research in this direction, and can also be used in lecture courses and practical classes on the history and practice of shaping furniture.